Londa Schiebinger e Claudia Swan (eds.), Colonial Botany Science, Commerce, and Politics in the Early Modern World (Altre Modernità, 2013)
(Philadelphia, University of Pennsylvania Press, 2005, 346 pp. ISBN 081-222-009-9 )di Agnese Visconti